Evolution of vertebrate postcranial complexity: axial skeleton regionalization and paired appendages in a Devonian jawless fish - Chevrinais, M.; Johanson, Z.; Trinajstic, Kate; Long, J.; Morel, C.; Renaud, C.; Cloutier, R. (Wiley-Blackwell Publishing Ltd., 2018)
One of the major events in vertebrate evolution involves the transition from jawless (agnathan) to jawed (gnathostome) vertebrates, including a variety of cranial and postcranial innovations. It has long been assumed that characters such as the pelvic girdles and fins, male intromittent organs independent from the pelvic girdles, as well as a regionalized axial skeleton first appeared in various basal gnathostome groups if not at the origin of gnathostomes. Here we describe the first occurrence of pelvic girdles and intromittent organs in the Late Devonian jawless anaspid-like fish Euphanerops longaevus Woodward (Miguasha Lagerstätte, eastern Canada), associated with a morphologically differentiated region of the axial skeleton. Morphological differentiation of the axial skeleton is also described for the first time in an extant jawless fish, the sea lamprey Petromyzon marinus Linnaeus. Our data indicate that regionalization of the axial skeleton occurred earlier in vertebrate evolutionary history than previously appreciated. This regionalization is coupled with modifications of the appendicular skeleton in Euphanerops. These new observations combined with a new phylogenetic analysis of early vertebrates provide a more precise understanding of how the appendicular and axial skeletons developed and evolved within vertebrate evolutionary history.